"1984": What Orwell could not predict. Proteomic analysis of his scripts. Issue 21 (9th June 2020) - Saravayskaya, Yana; Zilberstein, Gleb; Zilberstein, Roman; Zilberstein, Svetlana; Maor, Uriel; D'Amato, Alfonsina; Righetti, Pier Giorgio
Abstract: George Orwell, fighter for the Republican Army during the Spanish Civil War, was shot through the throat by a sniper on 20th May 1937 and nearly killed. After receiving only a summary external treatment, on the 29th, he was cured in a Barcelona hospital where he was infected by the Koch bacillus . After fleeing from Spain on 23rd June 1937, he repaired to his cottage in Wallington, Hertfordshire, wherefrom he wrote a letter to Sergey Dynamov, Editor of Soviet journal "Foreign Literature." This typewritten letter was analyzed by application of five EVA strips (ethylene vinyl acetate studded with strong cation and anion and with C8 and C18 resins; four on the corners and one over his signature), searching for biological traces. Upon elution of the captured biologicals, trypsin digestion and Orbitrap Fusion trihybrid mass spectrometer analyses, three of the five strips yielded clear traces of six unique proteins (via proteotypic peptides) of the tuberculosis bacterium . Additionally, MALDI TOF analysis of saliva of a tuberculosis patient and the EVA strip eluates gave a spectrum of 14 peptide bands (Mr 2700 to 6700 Da range) coincident between the two samples, thus, fully confirming Orwell's pathology. These results are attributed to saliva traces on Orwell's fingertips and to the fact that the letter was written on 2nd July 1937, when Orwell's pathology was at its peak.